Applicability of a colorimetric reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay for SARS-CoV-2 detection in high exposure risk setting - Nuchnoi P. (2023)
Objectives: During the third wave, the growing number of COVID-19 case clusters reported countrywide in Thailand demonstrated the rapidly evolving characteristics of SARS-CoV-2, the causative agent of the COVID-19 pandemic. The rapid spread of COVID-19 infections had been extensively reported in public areas and construction camps, as well as in congested communities with poor sanitation. High demand for SARS-CoV-2 genome testing and quick reporting by an hour for case identification and isolation characterizes the COVID-19 crisis in Thailand. This situation leads to an urgent need for alternative molecular tests which are reliable, rapid, and cost-effective. Methods: In this study, we assessed colorimetric reverse transcription loop-mediated isothermal amplification (RT-LAMP), using real-time reverse transcription-polymerase chain reaction (RT-PCR) as a reference standard, for active case finding in suspected (mostly asymptomatic) cases living in high-risk areas of Bangkok. Results: The diagnostic performance of the RT-LAMP compared with real-time RT-PCR in specimens from 549 Thais were computed in a real-world field study setting. Our study demonstrated that RT-LAMP achieved robust identification of SARS-CoV-2 infection, with a diagnostic sensitivity and specificity of 91.67% and 100%, respectively. Conclusion: RT-LAMP is a reliable assay for SARS-CoV-2 detection and is scalable for use in the emergency response to a nationwide pandemic, despite resource limitations. The RT-LAMP real-world data derived from this field study validate its potential use in laboratory practice. RT-LAMP is a good choice as a laboratory-based SARS-CoV-2 molecular test when real-time RT-PCR is not available.